PWE-062 Terminal Ileal Intubation Over A Five Year Period; Was It Useful?. (9th June 2014) - Ghuman, S; Khan, H
Abstract : Introduction: The value of routine ileoscopy during colonoscopy is unclear, but intubation of the terminal ileum (TI) is considered to be the main method of confirming completeness of colonoscopy. TI intubation rates are variable and intubation is often omitted due to time constraints and the perception of little added diagnostic value. Our aim was to assess the diagnostic yield of TI intubation during colonoscopies at our institution. Methods: A retrospective study was undertaken at our institution. Colonoscopy data over a 5 year period (1 st October 2007 to 30 th September 2012), were retrieved from the Endoscopy Reporting System database (Unisoft, Enfield, UK). Patients with ileo-caecal resection were excluded. Demographic data, TI pathology (endoscopic and histopathologic) and indications for colonoscopy were analysed. Results: 8016 colonoscopies were performed with a caecal intubation rate of 90.3%. The endoscopists were of different grades including gastroenterologists, colorectal surgeons and a nurse endoscopist. 206 with ileo-caecal resection were excluded. Mean age was 61 with a female preponderance at 52.6%. The TI w as intubated in 1845 (23.5%). Endoscopic TI pathology was identified in 42 patients (2.3%). Histology was available for 31, of which 23 (1.3%) had confirmed histological abnormalities. Diagnoses on ileoscopy included one adenocarcinoma, one carcinoid tumour, one metastatic malignant melanoma and 20 with terminal ileitis, of which, 6 had histological Crohn's disease. The most common indications in those with TI pathology were diarrhoea (15), abdominal pain (8) and rectal bleeding (8). Conclusion: Although the overall diagnostic yield was low, TI intubation identified significant pathologies requring further action, including three malignancies. Ileoscopy at colonoscopy is a simple manoeuvre, which, apart from quality assurance can identify important pathology. The most common indication in those with confirmed TI pathology was diarrhoea, therefore ileoscopy may have added diagnostic value in this context. Disclosure of Interest: None Declared.